PENGARUH UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MELALUI STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Muhammad Fuad Alamsyah; Alfin Akuba; Mohammad Afan Gaffar Bimbing (Jurnal Fokus Manajemen Bisnis, 2023)
Firm value is one of the benchmarks for investors before investing. Factors such as company size and capital structure can influence firm value. This study aims to determine the effect of company size using total assets and total sales on firm value with capital structure as an intervening variable in LQ45 companies in Indonesia for the 2016-2020 period. This quantitative research used the path analysis method for data analysis is Smart PLS version 3. The samples in this study were 43 companies registered in LQ45 for 2016-2020. The results show that firm size using total assets has a negative effect on firm value, and firm size using total sales was proven to have a positive effect on firm value. Firm size using total assets is proven to have a negative effect on capital structure, and firm size using total sales proved to have no effect on capital structure. Capital structure has a negative effect on firm value, while capital structure does not mediate the effect of firm size by using total assets and total sales on firm value.